Baseline Study of Microplastics in the Gastrointestinal Tract of Commercial Species Inhabiting in the Coastal Waters of Karachi, Sindh, Pakistan - Akhter, Najeeb; Panhwar, Sher Khan (Frontiers in Marine Science, 2022)
A microplastics (MPs) emergence study in pelagic and mesopelagic species was carried out to delineate coastal degradation and ecosystem status around the Karachi metropolis. Species of high commercial and ecological worth were sampled using a gillnet of 1.5 cm knot-to-knot mesh size in November and December 2021. In total twenty-six individuals including Liza subviridis (15), Thryssa dussumieri (3), Rastrelliger kanagurta (2), and Portunus sanguinolentus (6) were used to perceive MPs. A strong linearity between body length and MPs (R2 = 0.937, SE 0.071 and R2 = 0.928, SE 0.104) were calculated for L. subviridis and P. sangiuilatus, respectively. However, the data of T. dussummeiri and R. Kanagurta showed minimization failure. The MPs in GIT were extracted using direct observation under a sophisticated binuclear microscope and chemical digestion (KOH) together with wet peroxide oxidation (H2O2+FeSO4) methods. The MP materials were categorized as foam, film, fiber, fragment, and beads of three different sizes 170, 120, 100 μm in the stomach, intestine, and esophagus. Film-type MPs appeared frequently, whereas beads were rarely seen. It is hoped that this baseline research would help to minimize industrial release, recognize critical knowledge gaps, and demonstrate MP flux being released into the aquatic environment. The results will support mitigation of this emerging threat to the living resources around the Karachi coastal area.